2018
DOI: 10.1055/s-0038-1669947
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Pivotal Period in the Oral Feeding Progression of Preterm Infants

Abstract: The midpoint in the oral feeding progression is a pivotal period where setbacks are most likely to occur. This time frame can be used by clinicians to evaluate oral-motor skills for earlier provision of interventions to reduce the occurrence of oral feeding difficulties in this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
(58 reference statements)
1
1
0
Order By: Relevance
“…Even though the late group infants were exposed to more number of CPAP days suggesting more severe early lung disease, the use of supplemental oxygen need during the oral feeding period, at 36 weeks, and at hospital discharge were similar between the two groups. Similar to our study, Fucile et al [20], reported that setbacks in oral feeding progression are least likely to occur when the oral feeding attempt frequency reaches 6-8/day vs. 1-2 or 3-5 per day. In our center, we generally consider hospital discharge, once infant is 48h off-NG tube feeding if there are no other medical or social reasons.…”
Section: Discussionsupporting
confidence: 91%
“…Even though the late group infants were exposed to more number of CPAP days suggesting more severe early lung disease, the use of supplemental oxygen need during the oral feeding period, at 36 weeks, and at hospital discharge were similar between the two groups. Similar to our study, Fucile et al [20], reported that setbacks in oral feeding progression are least likely to occur when the oral feeding attempt frequency reaches 6-8/day vs. 1-2 or 3-5 per day. In our center, we generally consider hospital discharge, once infant is 48h off-NG tube feeding if there are no other medical or social reasons.…”
Section: Discussionsupporting
confidence: 91%
“…Their respiratory function will mature as preterm infants mature. Independent oral feeding is usually established near the time of discharge from NICU to home with coordination of sucking, swallowing, and breathing at a ratio of 1 : 1 : 1 or 2 : 2 : 1 [4].…”
Section: Introductionmentioning
confidence: 99%